SOCIAL VALUES IN PRIDE AND PREJUDICE NOVEL BY JANE AUSTEN - Hera Novrianita (ELTE Journal (English Languange Teaching and Education), 2020)
This research is aimed to identifythe intrinsic and the extrinsic elements and social values found in Pride and Prejudice novel by Jane Austen. This research is a descriptive qualitative study. In data collection, the researcher employed triangulation that presented three different techniques, namely documentation, observation, and interview. The results showed that, first, the story is a romantic story where Elizabeth Bennet and Mr.Darcy as the main characters. The setting of the story was inthe 19th century in Britain. Conflict; Mr.Darcy has much prejudice to Elizabeth and her family and makes some misunderstandings between them. Second, it was found that there are seven kinds of social values in Pride and Prejudice novel by Jane Austen. The social values found in the novel were honesty, human dignity,human rights,social equality,social class,religion, and responsibility.